Calcium sulfate floor base material and production process thereof

By adding excess calcium salt to the raw materials of calcium sulfate floor substrate and using a mixed gas of sulfur dioxide and chlorine, the problem of bubble elimination in the production of calcium sulfate floor substrate is solved, reducing production costs and improving the machinery of the material Strength and anti-static properties.

CN119219391AInactive Publication Date: 2024-12-31CHANGZHOU ABEITE COMPUTER ROOM EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411744767.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the production process of existing calcium sulfate floor substrates, vibration removal and pressure drainage are required, which takes a long time, resulting in high production costs, limiting their promotion and application.

Method used

Add excess calcium salt to the raw material of the calcium sulfate floor substrate, and use a mixed gas of sulfur dioxide and chlorine instead of air. The mixed gas reacts with the calcium salt through stirring to reduce the existence time of bubbles, eliminate the step of oscillation and elimination of bubbles, and Accelerate the maintenance steps.

Benefits of technology

The process of eliminating bubbles without oscillation is realized, which reduces moisture removal time, reduces production costs, and improves the mechanical strength and anti-static properties of calcium sulfate floor substrates.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a calcium sulfate floor base material and a production process thereof, and relates to the field of calcium sulfate floor base material preparation, according to the calcium sulfate floor base material and the production process thereof, an inorganic network is easily formed in the powder hydration process, an organic network is formed through epoxy resin curing, and the inorganic network and the organic network form an interpenetrating network; in addition, excessive calcium salt is added into the powder, mixed gas of sulfur dioxide and chlorine is filled in a closed environment to replace air to stir the slurry, and the mixed gas can be absorbed by water after entering the slurry, reacts with the calcium salt and does not exist in the form of bubbles for a long time, so that the calcium sulfate floor has the advantages of high compactness and high mechanical strength. And the slurry is stood in the mold, and precipitated liquid is discharged, so that the quality of a molded base material is not influenced by bubbles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a calcium sulfate floor substrate, in particular to a calcium sulfate floor substrate and a production process thereof. Background Art

[0002] Calcium sulfate, as the floor base material, has become the most widely used material in the elevated floor family due to its advantages in environmental protection, fire resistance, high strength, flatness, etc. The existing calcium sulfate floor is usually made of calcium sulfate as the main material, reinforced with mixed plant fiber, and made of pulse pressing base material, with ABS edging and galvanized steel plate as the bottom plate.

[0003] During the production of existing calcium sulfate floor substrates, it is necessary to gradually remove the air in the slurry through vibration equipment, and then slowly compact it through pressing equipment to remove moisture and form it, and then maintain it in a certain temperature and humidity environment to obtain a qualified floor substrate. The whole process is time-consuming, resulting in high production costs for the substrate, which limits the promotion and application of calcium sulfate flooring. If improvements can be made on the raw materials of the substrate to facilitate the removal of bubbles and excess moisture in the slurry, the production cost of the calcium sulfate floor substrate will be greatly reduced.

[0004] To this end, technicians in this field have proposed a calcium sulfate floor substrate and its production process, and made improvements in the raw material mixing of the calcium sulfate floor substrate, so that some additives react with water and bubbles to solidify after the molding is completed, eliminating the time-consuming oscillation to remove bubbles and slow pressure drainage, and accelerating the shade drying of the substrate in the curing step. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a calcium sulfate floor substrate and a production process thereof. Excess calcium salt is added to the substrate raw material, and a mixed gas of sulfur dioxide and chlorine is introduced to replace air. The mixed gas entering the slurry as stirred is absorbed by water and reacts with the calcium salt, so that the mixed gas will not exist in the form of bubbles for a long time like air, so there is no need to oscillate to remove the bubbles, and the quality of the formed substrate will not be affected.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A production process of a calcium sulfate floor substrate comprises the following steps:

[0007] Step 1: Mix and stir calcium sulfate hemihydrate, tricalcium silicate, perlite and chopped carbon fibers to obtain powder;

[0008] Step 2: Add cyclodextrin to water, add potassium hydroxide, and stir to dissolve; add 2-aminopyridine and cysteine ​​at 50-55°C; add epichlorohydrin dropwise at 60-65°C, and react for 1-2 hours; adjust the pH to 5-6, add anhydrous ethanol, and then stand, filter, purify, and dry to obtain mercaptocyclodextrin;

[0009] Step 3: Fill a closed container with a mixture of sulfur dioxide and chlorine, and sequentially add mercaptocyclodextrin and amine curing agent into the container and mix with the pulp, then add powder and water reducing agent, and quickly stir and mix; add water-based epoxy resin and curing accelerator, stir and mix to obtain a substrate material;

[0010] Step 4: pour the base material into a mold and roll it into shape; steam cure and dry; and obtain the antistatic calcium sulfate floor base material.

[0011] Preferably, the powder in step 1 comprises the following components: by weight, 100 parts of calcium sulfate hemihydrate, 15-25 parts of tricalcium silicate, 10-16 parts of perlite, and 5-10 parts of chopped carbon fibers.

[0012] Excessive tricalcium silicate is introduced into the powder, and its low hydration rate is utilized to reduce the hydration rate of the entire powder, thereby improving the hydration effect of water-saturated fibers in the pulp on the premature gel in the powder.

[0013] In addition, since the hydration rate of tricalcium silicate is slower than that of calcium sulfate hemihydrate, its hydration product can fill the voids of calcium sulfate hydrate, thereby increasing the compactness and enhancing the mechanical strength.

[0014] In addition, the addition of calcium salt helps absorb the bubbles in the slurry in the future, which not only reduces the steps of oscillation and exhaust, but also ensures the quality of the molded substrate.

[0015] Introducing chopped carbon fibers into the powder can, on the one hand, strengthen the inorganic network produced by the powder, and on the other hand, form an antistatic network with the quaternary ammonium salt groups, pyridine groups, etc. present in the organic network produced by the curing of epoxy resin, effectively enhancing the antistatic properties of the calcium sulfate floor substrate.

[0016] Preferably, the raw materials of the mercaptocyclodextrin in step 2 include the following components: 10 parts of cyclodextrin, 2-3.5 parts of 2-aminopyridine, 11-13 parts of cysteine, and 13-15 parts of epichlorohydrin, by weight.

[0017] Mercaptocyclodextrin is prepared by grafting cysteine ​​and aminopyridine onto cyclodextrin using epichlorohydrin as the linker, using the reaction of chlorine with hydroxyl groups and epoxy groups with amino groups. Mercaptocyclodextrin has carboxyl and mercapto groups, which delay the hydration reaction between calcium ions and sulfate ions and water, and has a slow-setting property, which can improve the hydration process and increase the strength. The mercapto groups it contains can cure epoxy resin at low temperatures, while the carboxyl groups can cure epoxy resin at higher temperatures, thereby producing different stage curing mechanisms and reducing curing stress. In addition, the grafted pyridine effectively enhances the antistatic effect.

[0018] Preferably, the substrate raw material in step 3 includes the following components: by weight, 100 parts of powder, 50-80 parts of pulp, 1-3 parts of water reducer, 6-12 parts of water-based epoxy resin, 2.3-2.8 parts of amine curing agent, 1.5-3 parts of mercaptocyclodextrin, and 0.5-1.2 parts of curing accelerator.

[0019] Preferably, the water reducer in step 3 is composed of a polycarboxylate water reducer and a naphthyl water reducer in a mass ratio of 5:3. The polycarboxylate water reducer can effectively slow down the entire hydration process, while the naphthyl water reducer enhances the later deceleration. The combination of the two can achieve a denser inorganic network.

[0020] The pulp is 5-8wt% industrial pulp. The fibers contained in the pulp can enhance the toughness and strength of the calcium sulfate floor. However, it is not advisable to introduce too much. First, if the water is oversaturated, too much fiber will be introduced, which will affect the hydration process; second, the fiber entanglement will lead to dispersion problems, resulting in reduced strength of the formed substrate. In addition, in order to improve the effect of pulp on hydration, tricalcium silicate, combined water reducer, and mercapto cyclodextrin are introduced into the raw materials to inhibit early hydration.

[0021] Preferably, the raw materials of the amine curing agent include, by weight, 10 parts of polyamino dendrimer, 1.4-1.6 parts of 2-chloroethyl isocyanate, 1.5-1.8 parts of isocyanate pyridine, and 3.2-3.5 parts of (N,N-dimethyl-3-aminopropyl)trimethoxysilane.

[0022] The polyamino dendrimer product is a four-arm product prepared by reacting ethylenediamine and pentaerythritol tetraacrylate, and can directly cure epoxy resin.

[0023] Furthermore, in order to enhance the antistatic property and mechanical strength of the calcium sulfate floor substrate, the polyamino dendrimer was modified to prepare an amine curing agent. The modification process was to first utilize the terminal amino group of the polyamino dendrimer to react with the isocyanate group, and partially graft 2-chloroethyl isocyanate and isocyanate pyridine; and then utilize the chlorine of 2-chloroethyl isocyanate to react with the tertiary amine in (N, N-dimethyl-3-aminopropyl)trimethoxysilane to produce a quaternization reaction.

[0024] The grafting of isocyanate pyridine increases the compatibility with mercaptocyclodextrin and the antistatic property; while the grafting of 2-chloroethyl isocyanate connects the grafting of (N,N-dimethyl-3-aminopropyl)trimethoxysilane, and the resulting quaternary ammonium salt group can improve the antistatic performance, and (N,N-dimethyl-3-aminopropyl)trimethoxysilane can increase the fluidity of the amine curing agent in the powder and improve the uniform dispersion of the powder. At the same time, the amine curing agent can enhance the toughness and bending performance of the calcium sulfate floor substrate because it is a four-arm product.

[0025] Preferably, the rolling forming process is: standing in the mold at room temperature for 30 to 60 minutes, removing the liquid precipitated on the surface, rolling at room temperature and 1 to 2 MPa for 20 to 30 minutes, rolling at 60 to 120°C and 5 to 8 MPa for 20 to 30 minutes; rolling at 120 to 160°C and 10 to 12 MPa for 10 to 15 minutes; steam curing time is 3 to 5 hours; drying conditions are: drying in the shade at room temperature for 20 to 30 hours.

[0026] Preferably, in step 3, a mixture of sulfur dioxide and chlorine is filled into a closed container, and the mixed gas dissolves in water instead of air, enters the slurry with stirring, is absorbed by the calcium salt in the raw material, and does not exist in the form of bubbles for a long time.

[0027] Preferably, the slurry after stirring in step 3 is discharged into a mold, and a calcium hydroxide solution is added to adjust the pH to 6-7. After standing, the liquid precipitated on the surface is removed, and then rolling is performed. The standing time ensures the absorption of bubbles in the slurry and facilitates the discharge of precipitated liquid from the surface. The pH is further adjusted to neutral by adding calcium hydroxide solution to avoid the mixed gas of sulfur dioxide and chlorine dissolving in water to cause an acidic environment that affects the fiber.

[0028] A calcium sulfate floor substrate is prepared by adding an excess of tricalcium silicate to the raw materials and stirring and mixing the raw materials in an environment of a mixed gas of sulfur dioxide and chlorine. After the mixed gas enters the slurry instead of air, it can be absorbed by the tricalcium silicate and will not exist in the slurry in the form of bubbles for a long time to affect the quality of the substrate.

[0029] The present invention discloses a calcium sulfate floor substrate and a production process thereof, which has the following beneficial effects:

[0030] 1. The calcium sulfate floor substrate and its production process, an inorganic network is easily formed during the hydration process of the powder, and an organic network is formed through the curing of the epoxy resin. The inorganic network and the organic network form an interpenetrating network, thereby effectively improving the density of the calcium sulfate floor and enhancing the mechanical strength. In addition, an excess of calcium salt is added to the powder, and a mixed gas of sulfur dioxide and chlorine is filled in a closed environment to replace air for stirring the slurry. After the mixed gas enters the slurry, it can be absorbed by water and react with the calcium salt. It will not exist in the form of bubbles for a long time. The slurry is left to stand in the mold and the precipitated liquid is discharged. There will be no bubbles that affect the quality of the molded substrate.

[0031] 2. The calcium sulfate floor substrate and its production process. Tricalcium silicate has the characteristic of low hydration rate and will not dissolve quickly during the mixing and stirring process. As the mixture of sulfur dioxide and chlorine is stirred, it enters the slurry to form bubbles. The bubbles are absorbed by water to generate hydrogen chloride and sulfuric acid, which react with tricalcium silicate to generate precipitation, which further absorbs the bubbles, making it difficult for the mixed gas to exist in the slurry in the form of bubbles for a long time. The slurry is left to stand in the mold to ensure that the bubbles are absorbed and the excess water is discharged directly from the top of the slurry. There is no influence of bubbles on the quality of the formed substrate. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The embodiment of the present invention discloses a calcium sulfate floor substrate and a production process thereof;

[0034] There are no special restrictions on the manufacturers of all raw materials involved in the present invention;

[0035] The purity of calcium sulfate hemihydrate is 95%, which is sourced from Shandong Longbang Gypsum Products Co., Ltd. and is ground through a 100-mesh sieve before use;

[0036] The purity of tricalcium silicate is 95%, which is sourced from Shandong Guohua Chemical Co., Ltd. and is used after being ground through a 150-mesh sieve;

[0037] The density of perlite is 2.4g / cm3, the particle size is 80 mesh, and it comes from Xinyang Yongkai Insulation Materials Co., Ltd.

[0038] Chopped carbon fiber, with a diameter of 5-10 μm, was sourced from Shanghai Lishuo Composite Materials Technology Co., Ltd.;

[0039] The model of polycarboxylate water reducer is SP-409, and the model of naphthalene water reducer is SSF-1000;

[0040] The cyclodextrin was β-cyclodextrin, CAS No. 7585-39-9, sourced from Zhengzhou Alpha Chemical Co., Ltd.;

[0041] The water-based epoxy resin model is WG827, which comes from Shandong Jiaying Chemical Technology Co., Ltd.

[0042] The CAS number of pentaerythritol tetraacrylate is 4986-89-4, the CAS number of 2-chloroethyl isocyanate is 1943-83-5, the CAS number of (N,N-dimethyl-3-aminopropyl)trimethoxysilane is 2530-86-1, the CAS number of 2-isocyanate pyridine is 4737-19-3, the CAS number of 2-aminopyridine is 504-29-0, and the CAS number of cysteine ​​is 52-90-4;

[0043] All ingredients in the application documents are added in parts by mass, indicating the mass relationship of each component.

[0044] Preparation of industrial pulp: waste paperboard and water are added to a pulper to be crushed to obtain industrial pulp with a fineness of 100 mesh and a concentration of 5-8wt%;

[0045] Preparation of polyamino dendrimer product: 20 parts of ethylenediamine and 8 parts of pentaerythritol tetraacrylate were added to 6.5 parts of methanol in sequence, reacted at 45°C for 15 hours, and the methanol and ethylenediamine were removed by vacuum distillation. The product was washed with ethyl acetate and then vacuum dried to obtain a polyamino dendrimer product.

[0046] Example 1: Preparation of a calcium sulfate floor substrate:

[0047] Step 1: 90 parts of calcium sulfate hemihydrate, 20 parts of tricalcium silicate, 12 parts of perlite, and 6 parts of chopped carbon fibers were mixed and stirred at 250 rpm for 30 minutes to obtain a powder;

[0048] Step 2: (1) Add 10 parts of cyclodextrin to 100 parts of pure water, add 8 parts of potassium hydroxide, and stir to dissolve; add 3 parts of 2-aminopyridine and 12 parts of cysteine ​​at 55°C; add 14 parts of epichlorohydrin dropwise at 55°C for 0.5 hours and react for 1 hour; adjust pH to 5.3, add anhydrous ethanol and let stand, filter, purify and dry to obtain thiol cyclodextrin;

[0049] (2) Add 10 parts of the polyamino dendrimer product to 1000 parts of toluene, add 1.5 parts of 2-chloroethyl isocyanate and 1.6 parts of 2-isocyanate pyridine at 0°C, and stir for 10 hours; add 3.4 parts of (N,N-dimethyl-3-aminopropyl) trimethoxysilane, 110 parts of N,N-dimethylacetamide, and 100 parts of toluene, stir at 80°C for 2 days, concentrate, add acetone to precipitate, filter, wash, and dry to obtain an amine curing agent;

[0050] Step 3: A mixture of sulfur dioxide and chlorine is filled in a closed container, 1.6 parts of mercaptocyclodextrin and 2.8 parts of amine curing agent are added to 76 parts of 6wt% industrial pulp in sequence, and stirred at 500rpm for 15 minutes; 100 parts of powder and 0.64 parts of water reducer are added, and stirring is continued for 15 minutes; 12 parts of waterborne epoxy resin and 0.25 parts of curing accelerator Uyhard-UR-300 are added, and stirring is continued for 10 minutes to obtain a substrate raw material; the water reducer is composed of a polycarboxylic acid water reducer SP-409 and a naphthyl water reducer SSF-1000 in a mass ratio of 5:3;

[0051] Step 4: Pour the substrate raw material into the mold, roll it at room temperature and 1.5Mpa for 30 minutes, roll it at 100℃ and 6Mpa for 20 minutes; roll it at 140℃ and 12Mpa for 10 minutes; then steam cure for 5 hours, dry it at 80℃ for 24 hours; and obtain the antistatic calcium sulfate floor substrate.

[0052] Example 2: Preparation of a calcium sulfate floor substrate:

[0053] Step 1: 90 parts of calcium sulfate hemihydrate, 20 parts of tricalcium silicate, 12 parts of perlite, and 6 parts of chopped carbon fibers were mixed and stirred at 250 rpm for 30 minutes to obtain a powder;

[0054] Step 2: (1) Add 10 parts of cyclodextrin to 100 parts of pure water, add 8 parts of potassium hydroxide, and stir to dissolve; add 3 parts of 2-aminopyridine and 12 parts of cysteine ​​at 55°C; add 14 parts of epichlorohydrin dropwise at 55°C for 0.5 hours and react for 1 hour; adjust pH to 5.3, add anhydrous ethanol and let stand, filter, purify and dry to obtain thiol cyclodextrin;

[0055] (2) Add 10 parts of the polyamino dendrimer product to 1000 parts of toluene, add 1.5 parts of 2-chloroethyl isocyanate and 1.6 parts of 2-isocyanate pyridine at 0°C, and stir for 10 hours; add 3.4 parts of (N,N-dimethyl-3-aminopropyl) trimethoxysilane, 110 parts of N,N-dimethylacetamide, and 100 parts of toluene, stir at 80°C for 2 days, concentrate, add acetone to precipitate, filter, wash, and dry to obtain an amine curing agent;

[0056] Step 3: Sulfur dioxide is filled in a closed container, 1.6 parts of mercaptocyclodextrin and 2.8 parts of amine curing agent are added to 76 parts of 6wt% industrial pulp in sequence, and stirred at 500rpm for 15 minutes; 100 parts of powder and 0.64 parts of water reducer are added, and stirring is continued for 15 minutes; 12 parts of waterborne epoxy resin and 0.25 parts of curing accelerator Uyhard-UR-300 are added, and stirring is continued for 10 minutes to obtain a substrate raw material; the water reducer is composed of a polycarboxylic acid water reducer SP-409 and a naphthyl water reducer SSF-1000 in a mass ratio of 5:3;

[0057] Step 4: Pour the substrate raw material into the mold, roll it at room temperature and 1.5Mpa for 30 minutes, roll it at 100℃ and 6Mpa for 20 minutes; roll it at 140℃ and 12Mpa for 10 minutes; then steam cure for 5 hours, dry it at 80℃ for 24 hours; and obtain the antistatic calcium sulfate floor substrate.

[0058] Example 3: Preparation of a calcium sulfate floor substrate:

[0059] Step 1: 90 parts of calcium sulfate hemihydrate, 20 parts of tricalcium silicate, 12 parts of perlite, and 6 parts of chopped carbon fibers were mixed and stirred at 250 rpm for 30 minutes to obtain a powder;

[0060] Step 2: Add 10 parts of cyclodextrin to 100 parts of pure water, add 8 parts of potassium hydroxide, and stir to dissolve; at 55°C, add 3 parts of 2-aminopyridine and 12 parts of cysteine; at 55°C, drop 14 parts of epichlorohydrin for 0.5 hours and react for 1 hour; adjust pH to 5.3, add anhydrous ethanol and let stand, filter, purify and dry to obtain thiol cyclodextrin;

[0061] (2) Add 10 parts of the polyamino dendrimer product to 1000 parts of toluene, add 1.5 parts of 2-chloroethyl isocyanate and 1.6 parts of 2-isocyanate pyridine at 0°C, and stir for 10 hours; add 3.4 parts of (N,N-dimethyl-3-aminopropyl) trimethoxysilane, 110 parts of N,N-dimethylacetamide, and 100 parts of toluene, stir at 80°C for 2 days, concentrate, add acetone to precipitate, filter, wash, and dry to obtain an amine curing agent;

[0062] Step 3: Fill chlorine gas into a closed container, add 1.6 parts of mercaptocyclodextrin and 2.8 parts of amine curing agent to 76 parts of 6wt% industrial pulp in sequence, and stir at 500rpm for 15 minutes; add 100 parts of powder and 0.64 parts of water reducer, and continue stirring for 15 minutes; add 12 parts of water-based epoxy resin and 0.25 parts of curing accelerator Uyhard-UR-300, stir for 10 minutes to obtain a substrate raw material; the water reducer is composed of a polycarboxylic acid water reducer SP-409 and a naphthyl water reducer SSF-1000 in a mass ratio of 5:3;

[0063] Step 4: Pour the substrate raw material into the mold, roll it at room temperature and 1.5Mpa for 30 minutes, roll it at 100℃ and 6Mpa for 20 minutes; roll it at 140℃ and 12Mpa for 10 minutes; then steam cure for 5 hours, dry it at 80℃ for 24 hours; and obtain the antistatic calcium sulfate floor substrate.

[0064] Example 4: Preparation of a calcium sulfate floor substrate:

[0065] Step 1: 90 parts of calcium sulfate hemihydrate, 10 parts of tricalcium silicate, 12 parts of perlite, and 6 parts of chopped carbon fibers were mixed and stirred at 250 rpm for 30 minutes to obtain a powder;

[0066] Step 2: (1) Add 10 parts of cyclodextrin to 100 parts of pure water, add 8 parts of potassium hydroxide, and stir to dissolve; add 3 parts of 2-aminopyridine and 12 parts of cysteine ​​at 55°C; add 14 parts of epichlorohydrin dropwise at 55°C for 0.5 hours and react for 1 hour; adjust pH to 5.3, add anhydrous ethanol and let stand, filter, purify and dry to obtain thiol cyclodextrin;

[0067] (2) Add 10 parts of the polyamino dendrimer product to 1000 parts of toluene, add 1.5 parts of 2-chloroethyl isocyanate and 1.6 parts of 2-isocyanate pyridine at 0°C, and stir for 10 hours; add 3.4 parts of (N,N-dimethyl-3-aminopropyl) trimethoxysilane, 110 parts of N,N-dimethylacetamide, and 100 parts of toluene, stir at 80°C for 2 days, concentrate, add acetone to precipitate, filter, wash, and dry to obtain an amine curing agent;

[0068] Step 3: A mixture of sulfur dioxide and chlorine is filled in a closed container, 1.6 parts of mercaptocyclodextrin and 2.8 parts of amine curing agent are added to 76 parts of 6wt% industrial pulp in sequence, and stirred at 500rpm for 15 minutes; 100 parts of powder and 0.64 parts of water reducer are added, and stirring is continued for 15 minutes; 12 parts of waterborne epoxy resin and 0.25 parts of curing accelerator Uyhard-UR-300 are added, and stirring is continued for 10 minutes to obtain a substrate raw material; the water reducer is composed of a polycarboxylic acid water reducer SP-409 and a naphthyl water reducer SSF-1000 in a mass ratio of 5:3;

[0069] Step 4: Pour the substrate raw material into the mold, roll it at room temperature and 1.5Mpa for 30 minutes, roll it at 100℃ and 6Mpa for 20 minutes; roll it at 140℃ and 12Mpa for 10 minutes; then steam cure for 5 hours, dry it at 80℃ for 24 hours; and obtain the antistatic calcium sulfate floor substrate.

[0070] Comparative Example 1: According to Example 1, tricalcium silicate is not introduced into the powder, and the powder is changed to: 90 parts of calcium sulfate hemihydrate, 12 parts of perlite, and 6 parts of chopped carbon fibers are mixed and stirred at 250 rpm for 30 minutes to obtain a powder; the remaining ingredients are the same as the steps.

[0071] Comparative Example 2: According to Example 1, the powder is not sealed in a container and is filled with a mixed gas environment of sulfur dioxide and chlorine for mixing and stirring; the remaining ingredients are the same as the steps.

[0072] Performance Test 1: The antistatic calcium sulfate floor substrate prepared in the embodiment and the comparative example was subjected to strength and internal bubble tests; a sample of 100×20×10 mm3 was taken, and the compressive strength was tested at 0.5 mm / min using a flexural and compression integrated testing machine; the surface resistivity was tested at 25°C and 65% RH with reference to GB / T 178-2001 "Concrete Bubble Agent"; the obtained data are shown in the following table:

[0073] sample Compressive strength (MPa) Internal bubble volume (cubic centimeters / cubic meters) Example 1 30.7 3.22 Example 2 25.5 7.51 Example 3 25.1 7.57 Example 4 27.8 5.57 Comparative Example 1 25.9 7.95 Comparative Example 2 26.6 8.87

[0074] Conclusion: The above experiments show that the calcium sulfate floor substrate prepared in the scheme has excellent compressive strength, up to 30.7MPa, and the internal bubble volume is 3.22cm 3 / m 3 ;

[0075] The data comparison between Example 1 and Comparative Examples 1-2 shows that the introduction of excessive tricalcium silicate effectively enhances the compressive strength of the calcium carbonate baseboard substrate;

[0076] The data comparison between Example 1 and Examples 2-3 shows that the simultaneous introduction of a mixed gas of sulfur dioxide and chlorine can effectively reduce the bubble content inside the calcium sulfate floor molding substrate;

[0077] The data comparison between Example 1 and Example 4 shows that adding an excessive amount of tricalcium silicate component to the powder can effectively reduce the bubble content inside the calcium sulfate floor molding substrate.

[0078] The calcium sulfate floor substrate and its production process are characterized in that an inorganic network is easily formed during the hydration of the powder, an organic network is formed through the curing of the epoxy resin, and the inorganic network and the organic network form an interpenetrating network, thereby effectively improving the compactness of the calcium sulfate floor and enhancing the mechanical strength. In addition, an excessive amount of calcium salt is added to the powder, and a mixed gas of sulfur dioxide and chlorine is filled in a closed environment to replace air to stir the slurry. After the mixed gas enters the slurry, it can be absorbed by water and react with the calcium salt, and will not exist in the form of bubbles for a long time. The slurry is left to stand in a mold, and the precipitated liquid is discharged, and there will be no bubbles to affect the quality of the molded substrate.

[0079] Furthermore, tricalcium silicate has the characteristic of low hydration rate and will not dissolve quickly during the mixing and stirring process. As the mixture of sulfur dioxide and chlorine enters the slurry during stirring, bubbles are formed. The bubbles are absorbed by water to generate hydrogen chloride and sulfuric acid, which react with tricalcium silicate to generate precipitates, which further absorb the bubbles, making it difficult for the mixed gas to exist in the slurry in the form of bubbles for a long time. The slurry is left to stand in the mold to ensure that the bubbles are absorbed and excess water is discharged directly from the top of the slurry, and there is no influence of bubbles on the quality of the molding substrate.

[0080] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A production process for a calcium sulfate floor substrate, characterized in that: The following steps are involved: Step 1: Mix and stir calcium sulfate hemihydrate, tricalcium silicate, perlite and chopped carbon fibers to obtain powder; Step 2: Add cyclodextrin to water, add potassium hydroxide, and stir to dissolve; add 2-aminopyridine and cysteine ​​at 50-55°C; add epichlorohydrin dropwise at 60-65°C, and react for 1-2 hours; adjust the pH to 5-6, add anhydrous ethanol, and then stand, filter, purify, and dry to obtain mercaptocyclodextrin; Step 3: Fill a closed container with a mixture of sulfur dioxide and chlorine, and sequentially add mercaptocyclodextrin and amine curing agent into the container and mix with the pulp, then add powder and water reducing agent, and quickly stir and mix; add water-based epoxy resin and curing accelerator, stir and mix to obtain a substrate material; Step 4: pour the base material into a mold and roll it into shape; steam cure and dry; and obtain the antistatic calcium sulfate floor base material.

2. The production process of calcium sulfate floor substrate according to claim 1, characterized in that: The powder in step 1 comprises the following components: by weight, 100 parts of calcium sulfate hemihydrate, 15-25 parts of tricalcium silicate, 10-16 parts of perlite, and 5-10 parts of chopped carbon fibers.

3. The production process of calcium sulfate floor substrate according to claim 1, characterized in that: The raw materials of the mercaptocyclodextrin in step 2 include the following components: 10 parts of cyclodextrin, 2-aminopyridine 2-3.5 parts, cysteine ​​11-13 parts, and epichlorohydrin 13-15 parts, by weight.

4. The production process of calcium sulfate floor substrate according to claim 1, characterized in that: The substrate raw materials in step 3 include the following components: by weight, 100 parts of powder, 50-80 parts of pulp, 1-3 parts of water reducing agent, 6-12 parts of water-based epoxy resin, 2.3-2.8 parts of amine curing agent, 1.5-3 parts of mercaptocyclodextrin, and 0.5-1.2 parts of curing accelerator.

5. The production process of calcium sulfate floor substrate according to claim 1, characterized in that: The water reducer in step 3 is composed of a polycarboxylate water reducer and a naphthyl water reducer in a mass ratio of 5:3, and the pulp is 5-8wt% industrial pulp.

6. The production process of calcium sulfate floor substrate according to claim 1, characterized in that: The raw materials of the amine curing agent include, by weight, 10 parts of polyamino dendrimer, 1.4-1.6 parts of 2-chloroethyl isocyanate, 1.5-1.8 parts of isocyanate pyridine, and 3.2-3.5 parts of (N,N-dimethyl-3-aminopropyl)trimethoxysilane.

7. The production process of calcium sulfate floor substrate according to claim 1, characterized in that: The rolling forming process is: standing in the mold at room temperature for 30 to 60 minutes, removing the liquid precipitated on the surface, rolling at room temperature and 1 to 2 MPa for 20 to 30 minutes, rolling at 60 to 120°C and 5 to 8 MPa for 20 to 30 minutes; rolling at 120 to 160°C and 10 to 12 MPa for 10 to 15 minutes; steam curing time is 3 to 5 hours; drying conditions are: drying in the shade at room temperature for 20 to 30 hours.

8. The production process of calcium sulfate floor substrate according to claim 1, characterized in that: In step 3, a mixture of sulfur dioxide and chlorine is filled into a sealed container. The mixed gas dissolves in water instead of air, enters the slurry with stirring, and is absorbed by the calcium salt in the raw material. It will not exist in the form of bubbles for a long time.

9. The production process of calcium sulfate floor substrate according to claim 1, characterized in that: The slurry after stirring in step 3 is discharged into the mold, and calcium hydroxide solution is added to adjust the pH to 6-7. After standing, the liquid precipitated on the surface is removed, and then rolling is performed.

10. A calcium sulfate floor substrate, characterized in that: Add an excess of tricalcium silicate to the raw materials and stir and mix them in an environment of sulfur dioxide and chlorine mixed gas. After the mixed gas enters the slurry instead of air, it can be absorbed by the tricalcium silicate and will not exist in the slurry in the form of bubbles for a long time to affect the quality of the substrate.